The Effect of Digital Literacy Competence Toward The Income of Home Industry Entrepreneurs (Universitas Negeri Semarang, 2023)
The purpose of this study is to measure the effect of digital literacy competence toward the income of home industry entrepreneurs or small home industries. The condition of the Covid-19 pandemic has changed people's lives, especially in the economic sector, which consequently reduces people's purchasing power, low income and unemployment. However, behind it all, online technology has begun to penetrate all fields in the economic sector. Small entrepreneurs or home industries must be ready to adapt to technology and digital literacy if they want to survive in their business. Digital technology can be used for marketing, production, and learning resources. This study employed a quantitative approach, descriptive statistical method with random sampling technique and the number of respondents is 50 home industry business units. The results of statistical calculations show Sig. (2-tailed) 0.05, Ha is accepted, then there is a significant difference in digital literacy competence on the income of home industry entrepreneurs. The conclusion of the analysis, is: The income of home industry entrepreneurs in this digitalization era is influenced by the ability of Information and data literacy, Communication and collaboration, Digital content creation, Safety, and Problem solving.